2010
DOI: 10.1021/jo102031b
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Sterically and Electronically Demanding Linear ω-Trifluoromethyl Containing Amino Acids via Alkylation of Chiral Equivalents of Nucleophilic Glycine and Alanine

Abstract: An operationally convenient, scalable asymmetric synthesis of linear, ω-trifluoromethyl-containing amino acids, which were not previously produced in their enantiomerically pure form, has been developed via alkylation of chiral equivalents of nucleophilic glycine and alanine. The simplicity of the experimental procedures and high stereochemical outcome (yields up to 90% and diastereoselectivity up to 99%) of the presented method render these fluorinated amino acids readily available for systematic medicinal ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 65 publications
0
25
1
Order By: Relevance
“…Wang et al. have previously reported a high diastereoselectivity (97 %), which was achieved with only 1.1 equivalents of NaOH . We have, however, obtained contradictory results.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…Wang et al. have previously reported a high diastereoselectivity (97 %), which was achieved with only 1.1 equivalents of NaOH . We have, however, obtained contradictory results.…”
Section: Resultscontrasting
confidence: 53%
“…Wang et al have previously reported ah igh diastereoselectivity (97 %), which was achieved with only 1.1 equivalents of NaOH. [45] We have, however,o btained contradictory results. Although the rate of the reactioni ncreased with an increased amount of NaOH, the diastereoselectivity between( S,S)-6 and (S,R)-6 was disappointingly low( Ta ble 1).…”
Section: Resultsmentioning
confidence: 94%
“…Structurally, the compound has an unusual fluorination pattern, such as v-CF 3 -containing side chain [114] linked to the diaryl ether core by forming the corresponding sulfonyl ester. Another cannabinoid receptor agonist reported by Bayer, BAY-59-3074 (41), sharing a similar structural scaffold, with the only difference in the substitutions on the ring A, exhibited noticeably lower agonist properties and acted as a CB1/CB2 partial agonist with antihyperalgesic and antiallodynic effects [115].…”
Section: Bay-38-7271 (Phase Ii)mentioning
confidence: 99%
“…One group of the methods is based on elaboration of functional groups in the already prearranged AA skeleton 2, such as additions of CF 3 radical to the terminal C=C bond [40,41] or biomimetic transamination [42,43]. However, a more general approach for synthesis of AA 1 includes alkyl halide alkylation of properly protected glycine derivatives 3 [44][45][46][47][48]. These reactions can be conducted under homogeneous [45][46][47][48], as well as PTC conditions [44].…”
Section: Introductionmentioning
confidence: 99%